New generic synonyms in the Palaeotropical genus Urothrips (Thysanoptera: Phlaeothripinae) with one new species from Seychelles - Ulitzka, Manfred R.; Mound, Laurence A. (Zootaxa, 2014)
Urothrips kobroi sp. n. is described from Seychelles, and reasons are given for considering Biconothrips Stannard and Coxothrips Bournier as new synonyms of Urothrips Bagnall. This genus now includes nine species, distributed between Africa and Australia, and a key to these species is provided.